International criminal law - O'Keefe, Roger, 1968- (2015)
International criminal law' provides a comprehensive overview of an increasingly integral part of public international law. It complements the usual accounts of the substantive law of those international crimes tried to date before international criminal courts and of the institutional law of those courts with in-depth analyses of fundamental formal juridical concepts such as an 'international crime' and an 'international criminal court'; with detailed examinations of the many international crimes provided for by way of multilateral treaty and of the attendant obligations and rights of states parties; and with sustained attention to the implementation of international criminal law at the national level. Direct, concise, and precise, 'International criminal law' should prove a valuable resource for scholars and practitioners of the discipline of international criminal law.
Part one. Foundational concepts and principles -- The international rules on national criminal jurisdiction -- The concept of an international crime -- The types of criminal court -- Part two. The substantive law of international crimes -- Crimes under customary international law -- The crimes -- Modes of responsibility -- Grounds for excluding responsibility -- Treaty crimes -- The crimes and their modes of responsibility -- The obligations and rights of states parties -- Part three. The suppression of international crimes -- Municipal law and courts -- Substantive law, jurisdiction, prosecution, and courts -- Immunity and inviolability -- Statutory limitation and amnesty -- International criminal courts -- The international criminal tribunals for the former Yugoslavia and Rwanda and their residual mechanism -- The Special Court for Sierra Leone and Residual Special Court for Sierra Leone -- The International Criminal Court.
Includes bibliographical references and index.
Keywords: International criminal law; International crimes; International criminal courts; 86.46 international criminal law; International crimes; International criminal courts; International criminal law; International criminal law; Textbooks (form)